Muscle activity and cardiovascular response during computer-mouse work with and without memory demands. - Finsen L; Søgaard K; Jensen C; Borg V; Christensen H (Ergonomics, 2001)
Computer-mouse work is characterized by repetitive movements combined with mental demands. The present purpose was to study how the body responded to simulated Computer Aided Design (CAD) work without memory demand and when a high short-term memory demand was introduced. Nine female subjects repetitively performed a task which involved 15 s of elevation of the right index and middle fingers followed by 6 s of rest. Every second time the fingers rested, the left index finger was required to type a six-figure number, either '123456' (without memory demand) or a random number shown half a minute before (with memory demand). After 7 min of performing the task without memory demand, the memory demand was introduced and continued for 1 h. Introduction of memory demand resulted in increased heart rate (77-->84 beats/min), blood pressure (systolic 129-->140 mmHg; diastolic 72-->79 mmHg) and forearm extensor muscle activity (wrist, 2.7-->4.5% EMGmax; finger, 5.6-->7.5% EMGmax) and finger flexor muscle activity (0.7 1.2% EMGmax) indicating increased co-contraction. Hereafter, muscle activity and cardiovascular response tended to decrease. Self-reported stress and rating of perceived exertion (RPE) for the right shoulder increased throughout the period. Two additional sub-studies were inlcuded, which focused on adaptation to the physical load, showing a decrease in muscle activity and arousal, and reintroduction of the memory load, showing a lower response as compared to the initial response. The practical consequences of the findings suggest that job content should have variable mental demands.